Sociology and Medicine Interactions and Emerging Disciplines - Jayasinghe, Saroj (European Scientific Journal, ESJ, 2020)
This brief essay places the work of Professor Siri Hettige in the context of understanding of social origins of health and disease. The origin of the term ‘social medicine’ dates to the French Revolution in 1848, which called for the medical profession to integrate knowledge in medical issues, population health, social factors and public policies. During this period, similar views were expressed elsewhere e.g. in Germany by Virchow’s famous statement that “medicine is a social science, and politics nothing but medicine on a grand scale”. In the early 20th century, another wave of social medicine originated in South America, a key figure being Salvador Allende. As the Minister of Health, he introduced these concepts to model the health services in Chile and later elected as the President. He was assassinated in a CIA sponsored military coup in 1973. In contrast, the early British and US traditions focused on a model where priority was on applying sociology in relation to individual behaviors. It was later that social structural determinants of health and diseases were addressed e.g. the Black Report of 1980. The US followed different trends, attempting to integrate concepts of the two disciplines (i.e. sociology in medicine) and studying the sociology of medicine (e.g. explaining health-seeking behaviors) and more recently, social epidemiology and politics of health. Professor Hettige’s extensive work covers almost all the above topics, trends and developments. His research publications and writings in the lay press have stimulated much discussion and contributed to sociopolitical changes in Sri Lanka. His name will be remembered as a pioneer in the field where sociology intersects with health in Sri Lanka and even in Asia.